Alpha-Lipoic Acid Mediates Clearance of Iron Accumulation by Regulating Iron Metabolism in a Parkinson’s Disease Model Induced by 6-OHDA - Tai, Shengyan; Zheng, Qian; Zhai, Suzhen; Cai, Ting; Xu, Li; Yang, Lizhu; Jiao, Ling; Zhang, Chunlin (Frontiers in Neuroscience, 2020)
The disruption of neuronal iron homeostasis and oxidative stress are related to the pathogenesis of Parkinson’s disease (PD). Alpha-lipoic acid (ALA) is a naturally occurring enzyme cofactor with antioxidant and iron chelator properties and has many known effects. ALA has neuroprotective effects on PD. However, its underlying mechanism remains unclear. In the present study, we established PD models induced by 6-hydroxydopamine (6-OHDA) to explore the neuroprotective ability of ALA and its underlying mechanism in vivo and in vitro. Our results showed that ALA could provide significant protection from 6-OHDA-induced cell damage in vitro by decreasing the levels of intracellular reactive oxygen species and iron. ALA significantly promoted the survival of the dopaminergic neuron in the 6-OHDA-induced PD rat model and remarkably ameliorated motor deficits by dramatically inhibiting the decrease in tyrosine hydroxylase expression and superoxide dismutase activity in the substantia nigra. Interestingly, ALA attenuated 6-OHDA-induced iron accumulation both in vivo and in vitro by antagonizing the 6-OHDA-induced upregulation of iron regulatory protein 2 and divalent metal transporter 1. These results indicated that the neuroprotective mechanism of ALA against neurological injury induced by 6-OHDA may be related to the regulation of iron homeostasis and reduced oxidative stress levels. Therefore, ALA may provide neuroprotective therapy for PD and other diseases related to iron metabolism disorder.